2013
DOI: 10.1039/c3cp50310k
|View full text |Cite
|
Sign up to set email alerts
|

Revealing surface oxidation on the organic semi-conducting single crystal rubrene with time of flight secondary ion mass spectroscopy

Abstract: To address the question of surface oxidation in organic electronics the chemical composition at the surface of single crystalline rubrene is spatially profiled and analyzed using Time of Flight - Secondary Ion Mass Spectroscopy (ToF-SIMS). It is seen that a uniform oxide (C42H28O) covers the surface while there is an increased concentration of peroxide (C42H28O2) located at crystallographic defects. By analyzing the effects of different primary ions, temperature and sputtering agents the technique of ToF-SIMS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…The origin of doping which shifts the Fermi level has not been addressed in this work. Previously, electronic states at 0.25–0.35 eV above the HOMO were identified and assigned to oxygen doping, while the structural defects were found to facilitate the oxidation . However, the structural defects were discussed as the sole origin of the same features in the photoluminescence spectra too .…”
Section: Resultsmentioning
confidence: 99%
“…The origin of doping which shifts the Fermi level has not been addressed in this work. Previously, electronic states at 0.25–0.35 eV above the HOMO were identified and assigned to oxygen doping, while the structural defects were found to facilitate the oxidation . However, the structural defects were discussed as the sole origin of the same features in the photoluminescence spectra too .…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that these oxide species of rubrene bind to different sites on the surface with rubrene peroxide preferentially being found at the sites of defects and rubrene oxide forming a more uniform covering of the surface. 16 As can be seen in Figure 2 there is a clear correlation between each of the ionic species tracked and the locations of the pillars. Several of the pillars can be identified even in the low count rubrene peroxide map.…”
Section: Resultsmentioning
confidence: 77%
“…21 A typical crystal can be seen in previous reports from our group along with a diagrammatic representation of the crystalline packing. 16,17 This study looks at the ab-plane surface. Crystals were mounted on an aluminium substrate using carbon paint.…”
Section: Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rubrene is considered the prototype single crystal organic semiconductor because of its relatively large charge carrier mobility (10-40 cm 2 /(V•s)) [10][11][12] and long exciton diffusion lengths (~4 microns) [13,14]. Oxidation properties of the single crystal have been studied in detail; in addition to evidence of an epitaxial native oxide layer [15], oxygen-related species have been observed uniformly on the surface and preferentially at structural defects [16], as well as under the surface [17], having accessed preferential channels into the bulk before spreading laterally [18]. Meanwhile, multiple oxygen incorporation mechanisms have been proposed, each with unique oxygen exposure methods, suggesting varying effects on rubrene device performance.…”
Section: Introductionmentioning
confidence: 99%